2007
DOI: 10.1521/suli.2007.37.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Which Helper Behaviors and Intervention Styles are Related to Better Short‐Term Outcomes in Telephone Crisis Intervention? Results from a Silent Monitoring Study of Calls to the U.S. 1–800‐SUICIDE Network

Abstract: A total of 2,611 calls to 14 helplines were monitored to observe helper behaviors and caller characteristics and changes during the calls. The relationship between intervention characteristics and call outcomes are reported for 1,431 crisis calls. Empathy and respect, as well as factor-analytically derived scales of supportive approach and good contact and collaborative problem solving were significantly related to positive outcomes, but not active listening. We recommend recruitment of helpers with these char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
134
3
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 19 publications
10
134
3
6
Order By: Relevance
“…However, Mishara et al found that helpers' sharing of their personal experiences could be helpful to callers and was associated with positive outcomes. Such self-disclosure could be used to demonstrate an understanding of the caller's situation and perhaps to compensate for the anonymous and disembodied nature of helpline contact (Mishara et al 2007). The non-directive, asymmetrical exchange relations of Samaritans' model of emotional support does not draw callers into a relationship of obligation or the commitment to an 'emotional ethic' or moral code (Bar-Lev 2008;Bar-Lev 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, Mishara et al found that helpers' sharing of their personal experiences could be helpful to callers and was associated with positive outcomes. Such self-disclosure could be used to demonstrate an understanding of the caller's situation and perhaps to compensate for the anonymous and disembodied nature of helpline contact (Mishara et al 2007). The non-directive, asymmetrical exchange relations of Samaritans' model of emotional support does not draw callers into a relationship of obligation or the commitment to an 'emotional ethic' or moral code (Bar-Lev 2008;Bar-Lev 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on Teleassistance or Tele-chekc with people at risk of suicide have shown that assessment intervention and, specifically, telephone support programmes, provide encouraging results and should be considered as a new instrument in the care of those at risk (184)(185)(186)(187)(188).…”
Section: Telephone Interventions In Suicide Preventionmentioning
confidence: 99%
“…Certains appelants réguliers connaissent même l'horaire des différents bénévoles et vont appeler en fonction de la disponibilité de la personne avec laquelle ils souhaitent parler (Licoppe, 2006). La fréquence d'appels de ces appelants peut aller jusqu'à plusieurs fois par jour et des centaines de fois durant l'année pour le même problème ou sans problème apparent (Metro Help Line, 1996 ;Mishara & al., 2007 ;Ricard & al., 2005 ;Watson, McDonald, & Pearce, 2006). Ces appelants ne démontrant, par le fait même, que très peu de volonté d'effectuer des changements dans leur vie (Gréer, 1976 ;Sawyer & Jameton, 1979).…”
Section: Parmi Les Divers Centres D'écoute Ou D'intervention Téléphonunclassified
“…Les CEIT sont d'ailleurs considérés comme des ressources essentielles parmi les services d'intervention psychosociale (Miller & al., 1984 ;Reese, Conoley & Brossart, 2002). Leur efficacité est toutefois difficile à mesurer car les contacts établis avec les appelants sont souvent de courte durée et anonymes, le suivi des impacts est donc difficile à évaluer (Leenaars & Lester, 2004 ;Mishara & al. 2007).…”
unclassified
See 1 more Smart Citation